Home Matters: Work and household predictors of smoking and cessation among blue-collar workers - Okechukwu, CA (2012)
OBJECTIVE: This study examined the joint influence of work- and household-related variables on smoking behavior among a population representative sample of blue-collar workers with live-in partners. METHODS: The study used data on 1,389 blue-collar workers from the Tobacco Use Supplement to the United States Current Population Survey 2002 to 2003 longitudinal overlap sample. Unadjusted and adjusted logistical regression analyses, which employed sampling and replicate weights to account for sampling design, were run to estimate independent and joint effects of the predictors. RESULTS: In adjusted analyses, partner smoking (OR=4.97, 95%CI=3.02–8.18) and complete and partial home smoking policy (OR=0.16, 95%CI=0.09–0.29 and OR=0.39, 95%CI=0.23–0.68, respectively) were significant predictors of smoking status, but worksite smoking policies and presence of a young child under 5 in the household were not (p>0.05). Baseline complete home smoking ban was a significant predictor of subsequent cessation (OR=3.49, 95%CI=1.19–10.23), while partner smoking status, workplace smoking policy, and the presence of a young child in the home did not predict cessation (p>0.05). CONCLUSION: Household-related variables were significant predictors of smoking status and cessation among blue-collar workers. Current efforts to decrease smoking in this group, which are mostly focused on work-related risk factors, should consider how to incorporate household risk factors.